PEMILIHAN BIBIT LELE UNGGUL DENGAN MENGGUNAKAN METODE WEIGHTED PRODUCT - Dasril Aldo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
One method of computing that is quite developed today is the method of decision support systems. A decision support system is required in order to have the ability to process a fast, targeted, and accountable in generating a decision. In the breeding and cultivation of catfish there are types of catfish seedlings are superior and not superior seeds, where the fish seeds should be selected and separated between superior and not superior. In the process of selecting superior catfish seedlings, the right selection mechanism is needed in order to produce the appropriate decisions as expected. The result of this research is the development of decision support system that can help the cultivation of catfish produce decision about the type of superior fish seedlings quickly and precisely.